Measured values of Ba/Ca in coral and coralline algae for seawater barium calibrations - Thomas J Williams; Christopher D Standish; Philippe Archambault; Jasmin A Godbold; Martin Solan; Orestis Katsamenis; Philip Basford; Gavin L Foster (PANGAEA, 2023)
A comprehensive georeferenced database of measured values of Ba/Ca in coral and coralline algae compiled from the scientific literature (1950-2021; http://www.webofknowledge.com, accessed 2022-09-30).
In: Williams, TJ et al. (2023): A global database of measured values of Li/Mg, Mg/Ca, Sr/Ca, Ba/Ca, U/Ca and Sr-U for coral and coralline algae paleoenvironment calibrations [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.962897